A new species of Longitarsus Latreille, 1825 from Mexico (Coleoptera, Chrysomelidae, Alticinae, Longitarsini) - Savini, Vilma; Escalona, Hermes E. (Zootaxa, 2005)
Longitarsus bethae sp. n. from Mexico is described, diagnostic illustrations are included; this species is under study as a biocontrol agent of Lantana camara L. (Verbenaceae), a worldwide weed.